Pengaruh Aplikasi Media Sosial Tiktok Terhadap Toleransi Beragama Bagi Mahasiswa UNNES Rombel E Angkatan 2022 - Septianto, Andhika Bagas; Nurharini, Atip; Ahadia, Carissa Nur; Baodin, Nur Adila binti; Lufiana, Rela (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine whether or not there is an influence of the Tiktok social media application on religious tolerance for UNNES Rombel E students Class of 2022. Researchers used sampling in the form of a simple random sampling technique. This sampling uses one independent variable (X) the Tiktok Social Media Application while the variable (Y) is the dependent variable, namely Religious Tolerance. Then the types of questionnaire data are primary data and secondary data. Data analysis techniques in this research, researchers used simple linear regression analysis techniques. The results of the research carried out obtained a significance value (sign.) of 0.200 greater than 0.05 so that the data was normally distributed. Through the use of the Glejser test, researchers obtained analysis results in the form of a sign X value (0.911) > 0.05. So it can be concluded that the influence of the Tiktok application on the tolerance of PGSD UNNES Rombel E 2022 students is not significant. So we got the result that the influence of Tiktok (X) on religious tolerance (Y) was only 7.6% and the rest of the religious tolerance was influenced by other things that the researchers did not know. So researchers can conclude based on the hypothesis results, there is no significant influence on the Tiktok application on religious tolerance. Thus, PGSD UNNES Rombel E 2022 students have been able to tolerate well by obtaining the percentage result of the influence of Tiktok (X) on religious tolerance (Y) of 7.6%, while 92.4% of the value of religious tolerance is influenced by other variables that cannot be researchers know.